Growth and bioactive phytochemicals of Panax ginseng sprouts grown in an aeroponic system using plasma-treated water as the nitrogen source - Jong-Seok Song (Nature Portfolio, 2021)
Abstract Ginseng (Panax ginseng Meyer) sprouts are grown to whole plants in 20 to 25 days in a soil-less cultivation system and then used as a medicinal vegetable. As a nitrogen (N) source, plasma-treated water (PTW) has been used to enhance the seed germination and seedling growth of many crops but has not been investigated for its effects on ginseng sprouts. This study established an in-situ system for N-containing water production using plasma technology and evaluated the effects of the PTW on ginseng growth and its bioactive phytochemicals compared with those of an untreated control. The PTW became weakly acidic 30 min after the air discharge at the electrodes because of the formation of nitrate (NO3 ‒) and nitrite (NO2 ‒) in the water. The NO3 ‒ and NO2 ‒ in the PTW, together with potassium ions (K+), enhanced the shoot biomass of the ginseng sprout by 26.5% compared to the untreated control. The ginseng sprout grown in the PTW had accumulated more free amino acids and ginsenosides in the sprout at 25 days after planting. Therefore, PTW can be used as a liquid N fertilizer for P. ginseng growth and phytochemical accumulation during sprouting under aeroponic conditions.